PHENOMENON OF EUPHEMISM AND ITS FUNCTIONS IN SPEECH - Alieva, Nargiza Nodirovna; Feruza , Urakova Botirjonovna (Educational Research in Universal Sciences, 2023)
This article provides an overview of the historical definition, motives, functions and linguistic tools of euphemism. It also talks about the most effective and common types of euphemisms.